Image quality and dose analysis for a PA chest X-ray: Comparison between AEC mode acquisition and manual mode using the 10 kVp 'rule' - Reis, Claudia; Goncalves, J.; Klompmaker, C.; Barbara, A.; Bloor, C.; Hegarty, R.; Lagrange, T.; Temming, N.; Sønnesyn, M.; Røkeness, H.; Yamasathien, A.; Hogg, P. (W.B. Saunders Co. Ltd., 2014)
Purpose: To compare the image quality and effective dose applying the 10 kVp rule with manual mode acquisition and AEC mode in PA chest X-ray. Method: 68 images (with and without lesions) were acquired using an anthropomorphic chest phantom using a Wolverson Arcoma X-ray unit. These images were compared against a reference image using the 2 alternative forced choice (2AFC) method. The effective dose (E) was calculated using PCXMC software using the exposure parameters and the DAP. The exposure index (lgM provided by Agfa systems) was recorded. Results: Exposure time decreases more when applying the 10 kVp rule with manual mode (50%–28%) when compared with automatic mode (36%–23%). Statistical differences for E between several ionization chambers' combinations for AEC mode were found (p = 0.002). E is lower when using only the right AEC ionization chamber. Considering the image quality there are no statistical differences (p = 0.348) between the different ionization chambers' combinations for AEC mode for images with no lesions. Considering lgM values, it was demonstrated that they were higher when the AEC mode was used compared to the manual mode. It was also observed that lgM values obtained with AEC mode increased as kVp value went up. The image quality scores did not demonstrate statistical significant differences (p = 0.343) for the images with lesions comparing manual with AEC mode. Conclusion: In general the E is lower when manual mode is used. By using the right AEC ionising chamber under the lung the E will be the lowest in comparison to other ionising chambers. The use of the 10 kVp rule did not affect the visibility of the lesions or image quality.